Tipologi Penanganan Potensi Bencana Longsor Berbasis Zonasi di Kawasan Permukiman Kota Semarang - Mardiansjah, Fadjar Hari; Herawati, Lutfi Adha; Zainrafipriyadi, Dizky Althaffaiz (Badan Riset dan Inovasi Daerah Kota Semarang, 2024)
Landslides are one of the main threats in Semarang City, especially in hilly areas and unplanned settlements. This study aims to analyse the typology of landslide disaster management based on zoning in residential areas of Semarang City. The methods used in this research include descriptive analysis and spatial analysis using Geographic Information System (GIS). The study identified 14 types of landslide vulnerability zones based on the level of potential vulnerability and frequency of occurrence, covering high to low vulnerability zones. Results show that areas with unplanned housing, poor drainage and high population density, such as in Kelurahan Pudak Payung and Sukorejo, have high landslide vulnerability and incidence. In contrast, some areas with planned housing and good drainage have a lower risk despite being potentially prone to landslides. From these results, more effective disaster mitigation strategies are recommended, including improved spatial planning, improved drainage infrastructure, as well as controlling settlement growth in landslide-prone zones to reduce the risk of future disasters.